Optimization of molding parameter effect to warpage and shrinkage based on plastic flow simulation software : swimming google - Lai, Si Ying (2010)
This thesis present about the optimization of molding parameter effect to warpage and shrinkage based on plastic flow simulation software: swimming goggles. The objective of this project is to study, analyze, and optimize the parameter that effect to warpage and shrinkage with using plastic flow simulation software. This project is using 3D scanner and draw swimming goggles in SolidWorks 2007. Swimming goggles lens is made by polycarbonate (PC) while swimming goggles frame is made by Acrylonitrile Butadiene Styrene (ABS). The injection molding parameters are optimized by using MoldFlow Plastics Insight (MPI) 5.0 software in order to get the best parameters with minimum warpage and shrinkage. The four injection molding parameter use is melt temperature, mold temperature, injection pressure and flow rate. The small changes of molding parameters will give higher impact to the plastic characteristics. The comparison between the types of analysis will be made. The comparison is between the deflections, fill times, and volumetric shrinkage. As the conclusion, the changes of injection molding parameters will affect the warpage of the swimming goggles.